Barriers of and strategies for shared decision-making implementation in the care of metastatic breast cancer: a qualitative study among patients and healthcare professionals in an Asian country - Lee, Ping Yein; Cheong, Ai Theng; Shariff Ghazali, Sazlina; Abdul Rashid, Aneesa; Ong, Siu Ching; Ong, Soo Ying; Alip, Adlinda; Sylvia, McCarthy; Chen, May Feng; Taib, Nur Aishah; Jaganathan, Maheswari; Ng, Chirk Jenn; et al. (John Wiley & Sons, 2022)
Background: Shared decision-making has been shown to improve the quality of life in metastatic breast cancer patients in high-literacy and high-resource settings. However, limited studies have examined the cultural preferences of metastatic breast cancer patients with shared decision-making implementation and the barriers encountered in an Asian setting where societal norms predominate and physician decision-making is at the forefront. This paper aims to identify (1) barriers to practising shared decision-making faced by healthcare professionals and patients and (2) strategies for implementing shared decision-making in the context of metastatic breast cancer management in Malaysia. Methods: We conducted a qualitative study involving 12 patients diagnosed with metastatic breast cancer, 16 healthcare professionals and 5 policymakers from surgical and oncology departments at public healthcare centres in Malaysia. Semi-structured in-depth interviews and focus group discussions were conducted. The interviews were recorded, transcribed verbatim and analysed using the thematic approach. Nvivo software was used to manage and analyse the data. Results: Five main themes emerged from the study: healthcare provider–patient communication, workforce availability, cultural and belief systems, goals of care and paternalism versus autonomy. Other strategies proposed to overcome barriers to implementing shared decision-making were training of healthcare professionals and empowering nurses to manage patients' psychosocial issues. Conclusion: This study found that practising shared decision-making in the public health sector remains challenging when managing patients with metastatic breast cancer. The utilization of decision-making tools, patient empowerment and healthcare provider training may help address the system and healthcare provider–patient barriers identified in this study.